Mitochondrial dynamics in Parkinson's disease: a role for α-synuclein - Pozo Devoto, Victorio M; Falzone, Tomas L (Disease models & mechanisms, 2017)
The distinctive pathological hallmarks of Parkinson's disease are the progressive death of dopaminergic neurons and the intracellular accumulation of Lewy bodies enriched in α-synuclein protein. Several lines of evidence from the study of sporadic, familial and pharmacologically induced forms of human Parkinson's disease also suggest that mitochondrial dysfunction plays an important role in disease progression. Although many functions have been proposed for α-synuclein, emerging data from human and animal models of Parkinson's disease highlight a role for α-synuclein in the control of neuronal mitochondrial dynamics. Here, we review the α-synuclein structural, biophysical and biochemical properties that influence relevant mitochondrial dynamic processes such as fusion-fission, transport and clearance. Drawing on current evidence, we propose that α-synuclein contributes to the mitochondrial defects that are associated with the pathology of this common and progressive neurodegenerative disease.
Keywords: mitochondriální dynamika; Mitochondrial Dynamics; Animals; alfa-synuklein; lidé; Parkinson Disease; Models, Biological; alpha-Synuclein; Parkinsonova nemoc; Humans; biologické modely; zvířata; Mitophagy; mitofagie